Glucocorticoids Induce Stress Oncoproteins Associated with Therapy-Resistance in African American and European American Prostate Cancer Cells - Woods-Burnham, Leanne (Sci Rep, 2018)
Glucocorticoid receptor (GR) is emerging as a key driver of prostate cancer (PCa) progression and therapy resistance in the absence of androgen receptor (AR) signaling. Acting as a bypass mechanism, GR activates AR-regulated genes, although GR-target genes contributing to PCa therapy resistance remain to be identified. Emerging evidence also shows that African American (AA) men, who disproportionately develop aggressive PCa, have hypersensitive GR signaling linked to cumulative stressful life events. Using racially diverse PCa cell lines (MDA-PCa-2b, 22Rv1, PC3, and DU145) we examined the effects of glucocorticoids on the expression of two stress oncoproteins associated with PCa therapy resistance, Clusterin (CLU) and Lens Epithelium-Derived Growth Factor p75 (LEDGF/p75). We observed that glucocorticoids upregulated LEDGF/p75 and CLU in PCa cells. Blockade of GR activation abolished this upregulation. We also detected increased GR transcript expression in AA PCa tissues, compared to European American (EA) tissues, using Oncomine microarray datasets. These results demonstrate that glucocorticoids upregulate the therapy resistance-associated oncoproteins LEDGF/p75 and CLU, and suggest that this effect may be enhanced in AA PCa. This study provides an initial framework for understanding the contribution of glucocorticoid signaling to PCa health disparities.